2021
DOI: 10.1016/j.ijhydene.2020.04.235
|View full text |Cite
|
Sign up to set email alerts
|

Toluene steam reforming over nickel based catalysts

Abstract: Steam reforming of toluene (SRT) has been studied initially in eight nickel-based catalysts where nickel (10 wt.%) was incorporated in different supports (olivine, Al2O3, MgO, LDH, ZrO2, CeO2 and natural sepiolite) by the incipient wetness impregnation method. Among them, nickel catalyst based on sepiolite exhibited a promising catalytic performance, with a high conversion of toluene (16%), high selectivity to hydrogen (68.4%) and low production of undesired by-products (CO, CH4, ethylene and benzene) at low t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Although Ni is an excellent catalyst for both electrochemical oxidation reaction and reforming reaction in producing hydrogen and syngas (H2 and CO) [44][45][46][47][48], Ni also prone to carbon deposition. Hence, Ni-free anode with alternative metal [6,17,49] and perovskites material [50,51] On the other hand, Singh et al [42] and Lay et al [61] reported no significant performance difference and higher amounts of carbon observed on the Sn doped cells compared to the undoped cells with either low steam to carbon ratio.…”
mentioning
confidence: 99%
“…Although Ni is an excellent catalyst for both electrochemical oxidation reaction and reforming reaction in producing hydrogen and syngas (H2 and CO) [44][45][46][47][48], Ni also prone to carbon deposition. Hence, Ni-free anode with alternative metal [6,17,49] and perovskites material [50,51] On the other hand, Singh et al [42] and Lay et al [61] reported no significant performance difference and higher amounts of carbon observed on the Sn doped cells compared to the undoped cells with either low steam to carbon ratio.…”
mentioning
confidence: 99%
“…Specifically, the peak at 430 °C corresponds to the reduction of NiO interacting with silica, 26,32,33 the peak at 620 °C is associated with the reduction of NiO–MgO on the surface and the peak at 750 °C relates to the reduction of NiO–MgO in the bulk. 34,35 Regarding the Ni/sepiolite catalyst treated at higher temperature (550 °C), a minor impact on the reduction temperatures is observed with similar peaks appearing at 450 °C, 630 °C and 740 °C. Based on the obtained TPR results and considering that before experimental testing the catalyst was reduced at 500 °C, the degree of Ni reduction was estimated to be 49% and 51% for the sample thermally treated at 500 °C and 550 °C, respectively.…”
Section: Resultsmentioning
confidence: 92%
“…moles of H 2 in the product gas maximum moles of H 2 allowed by stoichiometry (13) The maximum number of H 2 moles allowed by stoichiometry was calculated by considering toluene reforming reaction and that of WGS. Thus, H 2 potential is defined based on the maximum number of H 2 moles obtained when toluene is fully reformed to CO 2 and H 2 .…”
Section: Conversion (%) =mentioning
confidence: 99%
“…Tar model compounds have been widely used in order to ascertain the catalyst performance and determine suitable operating conditions. In this work, toluene was selected as a tar model compound because it is a stable aromatic structure, especially at relatively low temperatures, apart from being one of the major tar species in the biomass gasification [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation